Measuring Controller for Initial Information Processing - E. V. Skriabina; N. E. Sapozhnikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes to apply a combined measuring controller in order to solve a problem pertaining to redundancy of information transmitted from technical means which have passed  lifetime extension procedure at Atomic Power Stations (APS). The controller operates on the basis of digital and probabilistic forms of  information presentation that allows to obtain the best possible fit and combination of  accuracy, fast operation and hardware capacity.